2007
DOI: 10.1111/j.1365-2222.2007.02863.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to cross‐reactive carbohydrate determinants in relation to alcohol consumption

Abstract: CCD-specific IgE is prevalent in heavy drinkers, and is associated with positive IgE to pollens and Hymenoptera venoms. Specific IgE results should be interpreted with caution in heavy drinkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 40 publications
7
47
3
1
Order By: Relevance
“…This is in line with findings of 2 studies from the northwestern part of the Iberian peninsula (parts of Spain [9] and Portugal [8]). Thus, the association between alcohol and CCD sensitization seems to be universal and independent of cultural (e.g.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is in line with findings of 2 studies from the northwestern part of the Iberian peninsula (parts of Spain [9] and Portugal [8]). Thus, the association between alcohol and CCD sensitization seems to be universal and independent of cultural (e.g.…”
Section: Discussionsupporting
confidence: 79%
“…The factors that increase the risk of CCD sensitization are not entirely known [2]. CCD sensitization has been found to be associated with alcohol consumption in studies in the regions of Spain and Portugal in the northwest of the Iberian peninsula, where wine is the preferred alcoholic beverage by far [8,9]. It is not known whether the association between alcohol and CCD sensitization is present in other regions with different climatic and environmental conditions as well as different patterns of alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%
“…McMillan et al on the other hand, found a decrease in IgG and IgM and an increase in IgA levels in alcoholics and smokers [25]. There are other studies also in which statistically significant increase in IgA was associated with alcohol abuse [5,23,26]. In the present study though IgA levels were increased, however, to find out its statistical significance large number of cases need to be studied.…”
Section: Resultscontrasting
confidence: 49%
“…A recent Korean study showed an increased prevalence of allergic sensitization to house dust mite in alcoholics [20]. There are few other studies also suggesting an association between increased IgE and allergic sensitization in alcoholics [22][23][24]. In control subjects who showed high total IgE levels (>500 IU/ml), specific IgE levels were measured against common allergens (house dust, tree, and food allergens) to detect an allergic component.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of information on allergic disease at baseline (in 1976–1978), we cannot investigate the role of alcohol in the development of new (incident) allergic disease. We have recently shown that persons who drink moderate to large amounts of alcohol have a significantly increased prevalence of IgE sensitization to cross-reactive carbohydrate determinants (CCDs) [28, 29]. In these studies, serum-specific IgE sensitization to CCDs was associated with false-positive serum-specific IgE sensitization to CCD-bearing allergens, such as pollens and latex.…”
Section: Discussionmentioning
confidence: 94%